2019
DOI: 10.2147/idr.s219544
|View full text |Cite
|
Sign up to set email alerts
|

<p>High Level Aminoglycoside Resistance And Distribution Of The Resistance Genes In <em>Enterococcus faecalis</em> And <em>Enterococcus faecium</em> From Teaching Hospital In Malaysia</p>

Abstract: BackgroundEnterococcus faecium and Enterococcus faecalis are among the predominant species causing hospital-acquired infections. Currently, enterococcal infections are treated using combination therapy of an aminoglycoside with cell-wall active agents, which led to high level aminoglycoside resistance (HLAR) and vancomycin resistance (VRE) among enterococci. The aim of this study was to determine the prevalence of HLAR and the distribution of the resistance genes among clinical E. faecalis and E. faecium isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 24 publications
(27 reference statements)
4
10
0
Order By: Relevance
“…In our study, E. faecalis was more predominant compared to E. faecium . A similar phenomenon was observed among clinical samples obtained in a hospital in Malaysia [ 13 ] and in raw poultry meat samples from Canada, Colombia and Sweden [ 14 ]. In contrast, studies conducted in Indonesia, Thailand, and Vietnam reported E. faecium to be the predominat species in samples of chicken feces [ 15 ].…”
Section: Discussionsupporting
confidence: 75%
“…In our study, E. faecalis was more predominant compared to E. faecium . A similar phenomenon was observed among clinical samples obtained in a hospital in Malaysia [ 13 ] and in raw poultry meat samples from Canada, Colombia and Sweden [ 14 ]. In contrast, studies conducted in Indonesia, Thailand, and Vietnam reported E. faecium to be the predominat species in samples of chicken feces [ 15 ].…”
Section: Discussionsupporting
confidence: 75%
“…We observed an increased prevalence of VRE when compared to recent studies within the same geographical region. Moussa and colleagues reported a 4% occurrence of VRE among the 75 enterococci strains obtained in Hospital Kuala Lumpur (HKL), all of which were E. faecalis [ 17 ]. An earlier study by Daniel et al .…”
Section: Discussionmentioning
confidence: 99%
“…The enterococci strains in our sample pool showed a slightly lower prevalence of HLAR (39%) compared to a similar study within the same region. A recent study in HKL documented 45–49% HLAR, concerning streptomycin resistance, among the enterococci strains [ 17 ]. In the HKL study, the aac(6′)-Ie-aph(2″)-Ia AME gene was most common among the HLAR enterococci, accounting for their high level of resistance to gentamicin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in a study conducted by Chakraborty et al (2015) in India, all isolates were sensitive to vancomycin, and minimal inhibitory concentration of vancomycin against all enterococcal isolates was ≤1 μg/mL [26] . High levels of aminoglycoside resistance have become a very serious problem in healthcare settings worldwide [34] . Therapeutic options for invasive enterococcal infections typically include an aminoglycoside (e.g., gentamicin, streptomycin, and tobramycin) in combination with a cell wall active agent (e.g., vancomycin).…”
Section: Resultsmentioning
confidence: 99%